KONSTRUKSI KERUKUNAN BERAGAMA PADA PLURALITAS MASYARAKAT DUSUN KERANING DALAM PENGARUSUTAMAAN MODERASI BERAGAMA - L. Eka M. Julianingsih P.; I Nyoman Murba Widana (Widya Sandhi Jurnal Kajian Agama Sosial dan Budaya, 2022)
This study aims to examine the factors that encourage the construction of religious harmony in the plurality space of the people of Dusun Keraning in the mainstreaming of religious moderation. This event is part of the community's awareness of accepting the differences that exist in people's lives. This study uses an interpretive qualitative type in order to find the factors that cause harmony in everyday life. The results of this study found that the harmony implemented by the people of Keraning Hamlet was based on an awareness of the existence of God Almighty as the creator of diversity that should be respected. Belief in the One and Only God in Pancasila, which has been made the basis of the state, is a guideline in building a culture of society that is tolerant and mutually respectful of existing differences so as to create a pattern of civilized social life. Harmony implemented by the community is characterized by a number of differences as a practice of religious moderation.